JIDĀL AL-QUR’ĀN SEBAGAI METODE DAKWAH: STUDI ULUMUL QUR’AN TERHADAP POLA ARGUMENTASI ILAHI - Tulus Fikram Hamawi; Syahrul Jamil; Jefri Ariansyah Putra; Ali Akbar; Edi Hermanto (PT. Hasba Edukasi Mandiri, 2026)
The concept of jidāl in the Qur’an represents a significant argumentative method that plays a strategic role in Islamic preaching (da‘wah). However, in contemporary practice, jidāl is often misunderstood as a form of confrontational and emotional debate, deviating from Qur’anic ethical principles. This study aims to examine the concept of jidāl al-Qur’ān as a method of da‘wah by focusing on the divine patterns of arguentation embedded within Qur’anic verses. This research employs a qualitative approach through library research, utilizing a thematic exegesis (tafsīr mawḍū‘ī) method. Primary data are derived from the Qur’an and classical tafsir works, including Jāmi‘ al-Bayān by al-Ṭabarī, Tafsīr Ibn Kathīr, Al-Jāmi‘ li Aḥkām al-Qur’ān by al-Qurṭubī, and Mafātīḥ al-Ghayb by Fakhr al-Dīn al-Rāzī. Secondary data consist of literature on Qur’anic studies and contemporary Islamic communication. The analysis involves identifying relevant verses on jidāl, classifying their forms, and examining their argumentative structures and purposes. The findings indicate that jidāl al-Qur’ān is a da‘wah method grounded in rational argumentation, ethical communication, and persuasive engagement. The Qur’an employs various argumentative techniques, such as rhetorical questioning, analogy (qiyās), logical affirmation (taqrīr), and moral reminders (tazkīr), aiming to guide humanity toward truth without coercion. Furthermore, the Qur’an distinguishes between praiseworthy (jidāl maḥmūd) and blameworthy (jidāl madhmūm) argumentation, emphasizing the principle of jidāl billatī hiya aḥsan as stated in Q.S. An-Naḥl:125. This study concludes that jidāl in the Qur’an is not merely a debate technique but a systematic, ethical, and transformative method of communication in da‘wah. In the contemporary context, this concept is highly relevant as a solution to the crisis of argumentative ethics, particularly in digital spaces marked by polarization and discursive conflict. Therefore, revitalizing the Qur’anic method of jidāl is essential in fostering constructive and value-based dialogue in modern society.